Does Female Education have a Bargaining Effect on Household Welfare? Evidence from Ghana and Uganda - Raymond B. Frempong; David Stadelmann (Center for Research in Economics, Management and the Arts (CREMA), 2017)
Female education and its potential to empower women in the development process have engaged the interest of policy makers and academics over the years. By employing individual level data from Ghana and Uganda, we analyze whether female education has a direct bargaining effect on six household welfare indicators: child labor and school enrollment; food expenditure and nutrition intake; female labor force participation and fertility rates. The empirical results indicate that both, the level of the wife and her husband's education, are significant determinants of household welfare. However, the wife's education has no larger effect than that of her husband's, and the relative bargaining position of the wife, at most, has negligible effects on the welfare indicators studied. Further robustness analysis largely confirms our findings. We conclude that, whilst female education has the potential to enhance household welfare, the effect does not necessarily work though enhanced bargaining power.
Keywords: I2; J13; J16; 330; Women Empowerment; Intra-household Bargaining; Household Welfare; Ghana; Uganda